The science question in feminism - Harding, Sandra G. (Cornell University Press, 1986)
Can science, steeped in Western, masculine, bourgeois endeavors, nevertheless be used for emancipatory ends? In this major contribution to the debate over the role gender plays in the scientific enterprise, Sandra Harding pursues that question, challenging the intellectual and social foundations of scientific thought.Harding provides the first comprehensive and critical survey of the feminist science critiques, and examines inquiries into the androcentricism that has endured since the birth of modern science. Harding critiques three epistemological approaches: feminist empiricism, which identifies only bad science as the problem; the feminist standpoint, which holds that women's social experience provides a unique starting point for discovering masculine bias in science; and feminist postmodernism, which disputes the most basic scientific assumptions. She points out the tensions among these stances and the inadequate concepts that inform their analyses, yet maintains that the critical discourse they foster is vital to the quest for a science informed by emancipatory morals and politics.
Keywords: approches et analyses; cours; discipline; fem1000; point de vue situé; premier cycle; rapports sociaux de sexe; ressource en ligne; sciences humaines; épistémologie

Learning from the outsider within: The sociological significance of black feminist thought - Hill Collins, Patricia (Social Problems, 1986)
Keywords: afro-féminisme; amériques; approches et analyses; cours; discipline; fem1000; féminismes noirs; intersectionnalité; point de vue situé; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; épistémologie; états-unis